An Effective Neutrosophic Approach for Group Decision-Making in College English Teaching Quality Evaluation - Bin Xie (Neutrosophic Sets and Systems)
College English holds great importance in Chinese universities as one of the largest, most influential, and highly regarded foundational courses. Despite significant progress in reforming college English teaching (CET), its effectiveness has faced widespread criticism. To ensure and enhance the quality of CET, it is essential to explore the establishment of a quality evaluation mechanism. One such mechanism is the multiple attribute group decision-making (MAGDM) approach. Recently, the Exponential TODIM (ExpTODIM) and TOPSIS techniques have been employed to address MAGDM challenges. To capture uncertain data during the evaluation process, interval neutrosophic sets (INSs) are administrated as a valuable tool. This study introduces the interval neutrosophic number Exponential TODIM-TOPSIS (INN-ExpTODIM-TOPSIS) approach to address MAGDM using INSs. Eventually, a numerical study for CET quality evaluation is administrated to validate the INN-ExpTODIM-TOPSIS approach for evaluating the quality of CET.